No Contest Pleas as a Response to False Guilty Pleas in Canada - Sherrin, Christopher (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2024)
False guilty pleas are a major source of wrongful convictions. They are also probably inevitable; innocent accused have powerful reasons for resolving their cases short of trial. Given this, it might be wise to add the plea of no contest to the Canadian criminal justice system. A no contest plea could offer advantages for innocent accused, including the opportunity to obtain a reduced sentence without having to publicly (but falsely) admit guilt. It could also bring benefits to the system itself. It could come with some social costs, but those costs might not outweigh the benefits. This paper seeks to encourage discussion of the idea of a contest plea by analyzing its pros and cons.